PROBLEMATIKA PADA TATARAN KURIKULUM MATA PELAJARAN BAHASA INDONESIA SMP - Aji Jehan Fellani; Ahmad Feisal Riza; Heri Isnaini (Jurnal Kajian dan Penelitian Umum, 2023)
This research was conducted to understand the problems of Indonesian language subjects in junior high schools after the implementation of the new curriculum by the government, namely the independent curriculum. Public junior high schools in Batujajar District will only implement this new curriculum in the new academic year in July 2023. The results obtained show that more teachers are not ready to implement this new curriculum due to inadequate infrastructure in schools and a lack of knowledge about how to implement this new curriculum. From the results of the questionnaires that were distributed, it turned out that there were still teachers who did not really understand the 2013 curriculum which had been implemented so far in schools. The conclusion obtained is that not all teachers know that the government has provided online training services which can be accessed free of charge. The local government also needs to help provide socialization and understanding to teachers so that the independent curriculum can be implemented in the classroom.